Association between Physical Activity and Stress among Adolescents: The Role of Social Support - Emilía Sólrún Aradóttir 1996- (2024)
Physical activity (PA) and social support have been positively correlated with each other, and both have been negatively correlated with perceived stress. This study aimed to establish these correlations and to see if social support among adolescents had a mediating effect on the relationship between PA and perceived stress. The study consisted of 195 participants who were students at an upper secondary school in Iceland. The participants self-reported data on all variables. A significant negative correlation was found between PA and stress, as well as between social support and stress. This means that adolescents who are more physically active and perceive more social support perceive less stress. However, a statistical relationship was not found between PA and social support, which is not in line with prior research. Additionally, this study did not find a mediating effect of social support on the relationship between PA and perceived stress. Even so, it was concluded that taking part in PA and having more social support could be a buffer for adolescents perceived stress because of the negative correlation between both PA and stress and between social support and stress. Keywords: Social support, physical activity, stress, adolescence Hreyfing og félagslegur stuðningur hafa jákvæða fylgni við hvort annað og bæði hafa neikvæða fylgni við streitu. Markmið þessarar rannsóknar var að staðfesta þessi sambönd og kanna hvort að félagslegur stuðningur hefði miðlunaráhrif á sambandið á milli hreyfingar og félagslegs stuðnings hjá unglingum. Þátttakendur í rannnsókninni voru 195 menntaskólanemar á fyrsta ári sem svöruðu sjálfsmatslistum varðandi allar breyturnar. Fylgni var notuð til þess að mæla samband á milli breytanna. Niðurstöðurnar voru að marktæk neikvæð fylgni var á milli hreyfingar og streitu, einnig á milli félagslegs stuðnings og streitu. Það eru því þeir unglingar sem hreyfa sig meira og upplifa meiri félagslegan stuðning sem upplifa minni streitu. Ekki var tölfræðileg fylgni á milli hreyfingar og ...